The Effect of Family Environment and Learning Achievement on the Students’ Interest of Continuing Education to Higher Education at Technology Senior High School Pekanbaru - Apriliani, Pingki; Indrawati, Henny; Haryana, Gani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2024)
This paper discusses a phenomenon or situation encountered at SMA Technology Pekanbaru where there is a problem of low student interest in continuing their education to higher education. Meanwhile, fostering student interest in continuing their education to higher education is one of the efforts to improve the quality of education in order to create qualified human resources in their education and for a good career in the future. Therefore, this study was conducted to determine the effect of family environment and learning achievement on student interest in continuing education to college level at SMA Technology Pekanbaru. The research uses descriptive research methods with a quantitative approach. The research was conducted at SMA Technology Pekanbaru at Jl. Kubang Raya KM.1.5 Tuah Madani Village Tampan district Pekanbaru, which was carried out from June - November 2022. The research population was 43 students of class XI and XII at SMA Technology Pekanbaru in the academic year 2022/2023 so that all population is a sample. Data collection was carried out using questionnaires and documentation. Data analysis used was descriptive analysis and multiple regression analysis, which reviously passed the prerequisite analysis test. Based on the research result, it is obtained that the family environment and learning achievement have a positive and significant effect on the students’ interest in continuing education to college students at SMA Technology Pekanbaru. This means that family support and a good level of student achievement will increase students' interest in continuing their education to college.